A Pedestrian Exposure Model for the California State Highway System. Issue 4 (April 2019) - Griswold, Julia B.; Medury, Aditya; Schneider, Robert J.; Amos, Dave; Li, Ang; Grembek, Offer
For this study, we developed one of the first statewide pedestrian exposure models, using log-linear regression to estimate annual pedestrian crossing volumes at intersections on the California State Highway System. We compiled a database of more than 1, 200 count locations, one of the largest ever used to create a pedestrian volume mode. We initially evaluated 75 explanatory variables for the model. The final model is based on the three land-use variables (employment density, population density, number of schools), four roadway network variables (number of street segments, intersections with principal arterial and minor arterial roadways, and four-way intersections), and the U.S. Census Bureau's American Community Survey journey-to-work walk mode share that are readily available or fairly easy to create using basic geographic information system analysis. The resulting pedestrian volume model was used to estimate annual crossing volumes at more than 12, 000 intersections along the California State Highway System. This is one of the first statewide pedestrian volume models, and California may represent the largest jurisdiction to date to adopt a single, system-wide pedestrian volume model.